Comprehensive insights into the preferential precipitation of carbonates of magnesium in magnesium air fuel cell system - Sangeetha, Vivekanandan; Koshy, Rinu Anna; Kuppurangan, Gunaseelan; Gangadharan, Praveena (Frontiers in Environmental Chemistry, 2025)
Source separated urine comprises nitrogen, phosphorus, and potassium which are essential nutrients for plant growth. Although numerous methods and techniques exists to recover these nutrients from urine, factors such as chemical addition, high cost, operational complexities, and energy consumption limit their widespread adoption. Of late, magnesium air fuel cell (MAFC) has emerged as a promising candidate for concurrent nutrient recovery and energy production from source separated urine, owing to its electrochemical spontaneity. In our previous study, we investigated the concurrent resource (nutrient and energy) recovery from real source separated urine, where the preferential formation of magnesium carbonates (nesquehonite, MgCO3.3H2O) was observed. It was hypothesised that, bicarbonate (HCO3−) ions resulting from urea hydrolysis compete with phosphate (PO43−) ions to react with magnesium (Mg2+) ions. The objectives of this study were formulated to investigate the preferential formation of magnesium carbonates. To explore the influence of HCO3− ions on struvite formation, experiments were conducted with molar ratio from Mg2+: NH4+: PO43−: HCO3− = 1:1:1:1 to the real urine condition (Mg2+: NH4+: PO43−: HCO3− = 1:90:1:120). The experiments were conducted using both MAFC and sacrificial chemical precipitation (sacrificial chemical addition) methods. The recovered precipitates were characterised using X-Ray diffraction. The investigation revealed that the presence of HCO3− ions at a molar ratio > 1.5 hinders the struvite formation and imparts an amorphous nature to the precipitates. Additionally, a techno-economic assessment of MAFCs as a resource recovery system revealed that, the magnesium anode cost accounted for 47% of the capital expenditure (CAPEX). Furthermore, the revenue generation contributed to 0.85% of the total expenditure, emphasizing the need to increase the value proposition of source separated urine through recovery of additional nutrients and water.